Bronchopulmonary dysplasia: Clinical practices in five Portuguese neonatal intensive care units - Guimarães,H (2010)
With the advent of surfactant, prenatal corticosteroids (PNC) and advances in technology, the survival rate of extremely low birth weight (ELBW) infants has improved dramatically. Rates of bronchopulmonary dysplasia (BPD) vary widely among neonatal intensive care units (NICUs) and many studies using multiple interventions have shown some improvement in BPD rates. Implementing potentially better practices to reduce BPD has been an effort made over the last few decades. Aim: To compare five Portuguese NICUs in terms of clinical practices in very low birth weight (VLBW) infants, in order to developbetter practices to prevent BPD. Patients and methods: 256 preterm neonates, gestational age (GA) < 30 weeks and/or birthweight (BW) < 1250g admitted to five Portuguese NICUs (centers 1 to 5) between 1st January 2004 and 31st December 2006, were studied. VLBW infants with major malformations, grade IV intraventricular haemorrhage in the first week of life and metabolic or neuromuscular disease were excluded. BPD was defined as oxygen dependency at 36 weeks of postconceptional age. We considered a practice to be improved as clinically significant whenever a decrease greater than 10% in the prevalence of BPD adjusted for the practice, GA and BW was achieved compared to BPD prevalence adjusted only for GA and BW. Results: The overall prevalence of BPD was 12.9%. Our results revealed that PNC use should be improved in centers 2, 4 and 5; fluid policy in center 5; oxygen therapy in centers 1 and 3 and sepsis prevention in centers 1 and 2. Patent ductus arteriosus (PDA) treatment should be improved in center 2. Conclusion: The implementation of potentially better practices to reduce lung injury in neonates in Portuguese NICUs, according to each NICU, must be addressed to increase the prescription of PNC, to use a lower FiO2, to be careful with fluid administration in the first weeks of life and to prevent PDA and sepsis. It is necessary to follow guidelines, recommendations or protocols to improve quality in the prevention of BPD.